Cumulative exposure to traumatic events and craving among women in residential treatment for substance use disorder: The role of emotion dysregulation and mindfulness disposition - Sanchez, Mariana; Amaro, Hortensia (Frontiers in Psychology, 2022)
Objective Strong evidence links exposure to traumatic life events with subsequent substance use disorders (SUD). Compared to men, women in SUD treatment are more likely to have a history of trauma, characterized in part by emotion dysregulation known to negatively influence treatment outcomes. Existing research has been conducted with predominantly male and non-Hispanic White samples, with an emphasis on adverse childhood experiences. Little is known about how exposure to cumulative traumatic events across the lifespan affects emotion dysregulation and how this may influence craving, particularly among racial and ethnic minoritized women with SUD. Mindfulness disposition may serve as a protective factor that could buffer the impact of trauma exposure and emotion dysregulation on substance use craving among underrepresented minoritized women with SUD. This study examined the association between cumulative exposure to traumatic events, emotion dysregulation, and mindfulness disposition on substance use craving in a sample of predominantly Hispanic and non-Hispanic Black women in residential treatment for SUD. Method Cross-sectional data were analyzed for a baseline sample of 241 women (56.96% Hispanic, 20.7% non-Hispanic White, 20.7% non-Hispanic Black; age: M = 32.11) entering a SUD residential treatment facility who agreed to participate in a parent randomized controlled trial. Results Findings indicated that greater cumulative exposure to traumatic events and emotion dysregulation were associated with higher levels of craving. Cumulative traumatic event exposure was indirectly associated with higher craving via lower levels in the mindfulness dimension of acting with awareness. Interaction effects also revealed greater exposure to traumatic events was associated with higher levels of craving among women with low and average (but not high) levels of mindfulness disposition. Conclusion These findings provide insight into the potential benefits of targeting emotion regulation and mindfulness-building strategies such as acting with awareness in interventions among racial-ethnically diverse women with SUD. These strategies may be particularly beneficial among those that have experienced extensive histories of trauma exposure. Overall, knowledge gained from the present study can be particularly valuable towards informing treatment models in minoritized groups that currently experience disparities in treatment utilization and outcomes.